Fluorescence quenching of (dimethylamino)naphthalene dyes Badan and Prodan by tryptophan in cytochromes P450 and micelles - Pospíšil, Petr; Luxem, Katja E; Ener, Maraia; Sýkora, Jan; Kocábová, Jana; Gray, Harry B; Vlček, Antonín; Hof, Martin (The journal of physical chemistry. B, 2014)
Fluorescence of 2-(N,N-dimethylamino)-6-propionylnaphthalene dyes Badan and Prodan is quenched by tryptophan in Brij 58 micelles as well as in two cytochrome P450 proteins (CYP102, CYP119) with Badan covalently attached to a cysteine residue. Formation of nonemissive complexes between a dye molecule and tryptophan accounts for about 76% of the fluorescence intensity quenching in micelles, the rest is due to diffusive encounters. In the absence of tryptophan, fluorescence of Badan-labeled cytochromes decays with triexponential kinetics characterized by lifetimes of about 100 ps, 700-800 ps, and 3 ns. Site mutation of a histidine residue in the vicinity of the Badan label by tryptophan results in shortening of all three decay lifetimes. The relative amplitude of the fastest component increases at the expense of the two slower ones. The average quenching rate constants are 4.5 × 10(8) s(-1) (CYP102) and 3.7 × 10(8) s(-1) (CYP119), at 288 K. Cyclic voltammetry of Prodan in MeCN shows a reversible reduction peak at -1.85 V vs NHE that becomes chemically irreversible and shifts positively upon addition of water. A quasireversible reduction at -0.88 V was observed in an aqueous buffer (pH 7.3). The excited-state reduction potential of Prodan (and Badan) is estimated to vary from about +0.6 V (vs NHE) in polar aprotic media (MeCN) to approximately +1.6 V in water. Tryptophan quenching of Badan/Prodan fluorescence in CYPs and Brij 58 micelles is exergonic by ≤0.5 V and involves tryptophan oxidation by excited Badan/Prodan, coupled with a fast reaction between the reduced dye and water. Photoreduction is a new quenching mechanism for 2-(N,N-dimethylamino)-6-propionylnaphthalene dyes that are often used as solvatochromic polarity probes, FRET donors and acceptors, as well as reporters of solvation dynamics.
Keywords: fluorescenční barviva; kinetika; Tryptophan; Models, Molecular; systém (enzymů) cytochromů P-450; tryptofan; fluorescenční spektrometrie; Fluorescence; Fluorescent Dyes; 2-naftylamin; voda; 2-Naphthylamine; micely; Archaeal Proteins; NADPH-Ferrihemoprotein Reductase; Water; fluorescence; archeální proteiny; Cytochrome P-450 Enzyme System; Bacterial Proteins; Spectrometry, Fluorescence; molekulární modely; NADPH-cytochrom c-reduktasa; Kinetics; Micelles; bakteriální proteiny